1998
DOI: 10.1002/chin.199847011
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Room Temperature Electrochemical Redox Reactions of the Defect Perovskite SrFeO2.5+x.

Abstract: structure structure (solids and liquids) D 2000 47 -011 Room Temperature Electrochemical Redox Reactions of the Defect Perovskite SrFeO 2.5+x . -The electrochemical and chemical oxidation of the defect perovskite SrFeO 2.5 to the cubic perovskite SrFeO 3 at ambient temp. in alkaline electrolyte is shown to be principally reversible. The oxidation occurs via the intermediate phases SrFeO 2.75 , SrFeO 2.87 , and SrFeO 3−δ (0≤δ≤0.003). The structure of the brownmillerite type parent phase is characterized by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Additionally, BM-SFO has a broad shoulder on the anodic scan that may be attributed to a two phase transitions from BM-SFO to SrFeO 2.75 as the oxide ion intercalation reaction progresses. 34 Figure 3b shows that the LSMO series has two pairs of redox peaks centered at −0.3 and −0.1 V vs Hg/HgO that are attributed to Mn 2+/3+ and Mn 3+/4+ transitions respectively, caused by OH − anion-based intercalation in agreement with our previous results. 15 We note that the LMO capacitance is lower than we reported previously 15 because VC A is used as a conductive support instead of a N-doped mesoporous carbon.…”
Section: ■ Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Additionally, BM-SFO has a broad shoulder on the anodic scan that may be attributed to a two phase transitions from BM-SFO to SrFeO 2.75 as the oxide ion intercalation reaction progresses. 34 Figure 3b shows that the LSMO series has two pairs of redox peaks centered at −0.3 and −0.1 V vs Hg/HgO that are attributed to Mn 2+/3+ and Mn 3+/4+ transitions respectively, caused by OH − anion-based intercalation in agreement with our previous results. 15 We note that the LMO capacitance is lower than we reported previously 15 because VC A is used as a conductive support instead of a N-doped mesoporous carbon.…”
Section: ■ Introductionsupporting
confidence: 91%
“…Comparing the three B-site series, the LSFO samples have the highest peak currents that suggest fast lattice oxygen diffusion rates, which is supported by the LSFO series' high oxygen vacancy concentrations. The redox peaks centered at E 1/2 ∼ −0.8 V vs Hg/HgO are attributed to OH − anion intercalation induced by Fe 2+/3+ and possibly Fe 3+/5+ transitions through Fe 4+ disproportionation as described by Dann et al 33 for x = 0, 0.2 33 and BM-SFO, 34 but LSFO64 shows the presence of a reversible redox peak centered at ∼−0.3 V vs Hg/HgO which is attributed to be the Fe 3+/4+ transition.…”
Section: ■ Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Nucleation energy barriers to these multiple phase transitions would slow down charge transfer kinetics, 41 thus requiring a large overpotential in both directions toward intercalation that explains the large observed peak separation in BM-SFO. 8 Related work by Nemudry et al 42 has identified the slow phase transformation of SrFeO 2.5 to SrFeO 3 occurring at ∼0.2 V vs Hg/HgO at a 1.5 mA g ox −1 current density. A small hump at x = 2.50 is observed during insertion, occurring at ∼0.4 V vs Hg/HgO, which agrees with Nemudry 42 after considering the iR drop and polarization resistance resulting from the ∼10× higher applied current.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 95%